Investigation of the preparation and performance of Ag-modified ZnO nanowall ultraviolet detector - Xiaoyang Wang; Juntang Dong; Shiguang Shang; Shiheng Xin; Shiping Li; Tingting Shao; Yanning Yang; Fuchun Zhang; Zeheng Ni (Journal of Advanced Dielectrics)
In this paper, silver (Ag) nanoparticle-modified zinc oxide (ZnO) nanowall photoconductive ultraviolet photodetector was prepared by using magnetron sputtering technology, electron beam evaporation method and hydrothermal method. The results showed that ZnO nanowalls exhibited a hexagonal wurtzite structure. ZnO nanowalls grew uniformly perpendicular to the substrate, and metallic Ag nanoparticles were uniformly attached to the surface of ZnO nanowalls, effectively improving the ZnO nanowall absorption capability in the ultraviolet light region. The dark current of the Ag-modified ZnO nanowall UV detector deposited by sputtering for 40[Formula: see text]s was 0.042[Formula: see text]mA, revealing a decrease of 44%. Under the irradiation of ultraviolet light with a wavelength of 325[Formula: see text]nm, the photocurrent reached 3.088[Formula: see text]mA, which increased by four times. The responsivity increased from 27.29 to 101.07[Formula: see text]mA/W, and the sensitivity increased from 8.07 to 73.52. In addition to the good repeatability and stability, the response time was reduced by 64%, and the recovery time was decreased by 50%.